2011
DOI: 10.1093/eurjhf/hfr133
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal haemodynamic response to exercise in heart failure with preserved ejection fraction

Abstract: AimsPeak oxygen uptake (VO 2 ) is diminished in patients with heart failure with preserved ejection fraction (HFpEF) suggesting impaired cardiac reserve. To test this hypothesis, we assessed the haemodynamic response to exercise in HFpEF patients. Methods and resultsEleven HFpEF patients (73 + 7 years, 7 females/4 males) and 13 healthy controls (70 + 4 years, 6 females/7 males) were studied during submaximal and maximal exercise. The cardiac output (Q c , acetylene rebreathing) response to exercise was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
209
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(234 citation statements)
references
References 33 publications
19
209
0
6
Order By: Relevance
“…83 In a different cohort, Bhella et al found that while QC reserve was depressed in HFpEF (as previously demonstrated by other groups), when normalized to VO2, HFpEF patients displayed an overly exuberant increase in QC, with markedly impaired AVO2diff reserve. 20 Those authors proposed the provocative conclusion that exercise capacity in HFpEF is limited by premature skeletal muscle fatigue and/or by metabolic/neural signals originating in muscle that stimulate excessive QC responses to exercise.…”
Section: Heart Rate and Rhythmmentioning
confidence: 99%
“…83 In a different cohort, Bhella et al found that while QC reserve was depressed in HFpEF (as previously demonstrated by other groups), when normalized to VO2, HFpEF patients displayed an overly exuberant increase in QC, with markedly impaired AVO2diff reserve. 20 Those authors proposed the provocative conclusion that exercise capacity in HFpEF is limited by premature skeletal muscle fatigue and/or by metabolic/neural signals originating in muscle that stimulate excessive QC responses to exercise.…”
Section: Heart Rate and Rhythmmentioning
confidence: 99%
“…The primary symptom in patients with chronic HFPEF is severe exercise intolerance, measured objectively as decreased peak exercise O 2 uptake (peak V O 2 ) (2,3,5,26,30,34,35,41), and this is associated with a reduced quality of life. Despite its importance, the pathophysiology of exercise intolerance in HFPEF is not well understood.Several lines of evidence suggest that in older HFPEF patients, noncardiac factors may contribute to reduced peak V O 2 and may be major contributors to the improvement in peak V O 2 after endurance exercise training (2,5,23,24,26,36,47,54). It is known that aging results in alterations in skeletal muscle, including a reduction in the relative number of type II fibers (40) and in capillary density (9), and that these are associated with a decline in physical performance (51).…”
mentioning
confidence: 99%
“…Several lines of evidence suggest that in older HFPEF patients, noncardiac factors may contribute to reduced peak V O 2 and may be major contributors to the improvement in peak V O 2 after endurance exercise training (2,5,23,24,26,36,47,54). It is known that aging results in alterations in skeletal muscle, including a reduction in the relative number of type II fibers (40) and in capillary density (9), and that these are associated with a decline in physical performance (51).…”
mentioning
confidence: 99%
“…The usefulness of the measurement of LV longitudinal systolic function was confirmed by Wenzelburger et al 36 who found a significantly lower mitral annular plane systolic excursion (MAPSE) at rest and mainly during exercise in 62 subjects with HFNEF compared to 36 control subjects. In HFNEF patients, other authors found significantly higher exercise pulmonary vascular resistance index 37 , systemic vascular resistance index 37 , lower exercise stroke volume index and cardiac index 37,38 , greater arterial stiffening 39,40 , and reduced arteriovenous oxygen difference 41,42 . In summary, despite many new potentially applicable diagnostic parameters or disturbances associated with exercise HFNEF, none have been sufficiently validated to diagnose exercise HFNEF.…”
Section: Other Hemodynamic and Functional Abnormalities With Potentiamentioning
confidence: 93%